(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
This study investigated the protective potentials of methanolic leaf extract of Ficus exasperata on sodium arsenate-mediated dyslipidemia and oxidative damage in the brain of rats. Twenty-eight rats were sorted into four groups containing seven rats each. Group A (control) received distilled water while 10 mg/kg bw of arsenic in form of sodium arsenate (As) was administered intraperitoneally to groups B, C and D. Group C and D were treated with oral administration of 100 mg/kg bw and 200 mg/kg bw of F. exasperata leaf respectively for 14 days. Arsenate administration resulted in dyslipidemia as shown by significant elevation (P<0.05) in total cholesterol, triglycerides, LDL-cholesterol and coronary heart disease risk ratio while it also reduced HDL-cholesterol in the rats. It also causes lipid peroxidation and oxidative damage in the brains of the rat with significant elevation of malondialdehyde level and decrease in levels of reduced glutathione, glutathione s-transferase, catalase and superoxide dismutase. Histology of the cortex region of brain of the rats treated with arsenate showed abnormal neuronal morphology with neuronal degeneration and necrosis. However, treatment with F. exasperata significantly reversed and attenuated the arsenatemediated biochemical alterations. We demonstrated in this study that F. exasperata leaf effectively protects against arsenate-induced dyslipidemia and oxidative damage in rat’s brain.